Seven languages in seven weeks : a pragmatic guide to learning programming languages - Tate, Bruce, 1965- (Pragmatic programmers., 2010)
Presents an introduction to the Ruby, Io, Prolog, Scala, Erlang, Clojure, and Haskell programming languages.